2007
DOI: 10.4152/pea.200806479
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of Diethanolamine on Corrosion of Mild Steel in 0.5 M Sulphuric Acidic Medium

Abstract: The inhibitory effect of diethanolamine (DEA) on corrosion of mild steel in 0.5 M H 2 SO 4 was investigated by various corrosion monitoring techniques. Galvanostatic polarization study revealed that this compound is a very good inhibitor. The inhibition efficiency (I%) varies in the range of 88.7% to 55.3 % for a concentration range of 10 -3 M to 10 -7 M at 303 K, respectively. A study of corrosion potential (E corr ) reveals that DEA is a mixed type inhibitor. DEA inhibited mild steel corrosion due to physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…The negative free energy change values substantiate that the adsorption of the chemical components on the metal surface is spontaneous, and the high stability of the adsorbed layer on the mild steel surface. It has been already reported that Gibbs free energy values between -49 kJ/mol and -58 kJ/mol are indicative of chemisorption [24]. The low free energy change values in the present case further confirm the physical nature of adsorption.…”
Section: Thermodynamic Studiessupporting
confidence: 85%
“…The negative free energy change values substantiate that the adsorption of the chemical components on the metal surface is spontaneous, and the high stability of the adsorbed layer on the mild steel surface. It has been already reported that Gibbs free energy values between -49 kJ/mol and -58 kJ/mol are indicative of chemisorption [24]. The low free energy change values in the present case further confirm the physical nature of adsorption.…”
Section: Thermodynamic Studiessupporting
confidence: 85%
“…5(b), isotherm fittings of the experimental and the predicted models, while in the modelled fittings indicated predominance of physical adsorption or physisorption [45]. The positive values of the lateral interaction factor, the Frumkin a-values in the experimental and the predicted models, bear indications that the adsorption energy is increased by the lateral attraction between the molecules in the adsorbed layer [40]. The results constitute reasons supporting the use of P. muellerianus leaf-extract as environmentally-friendly admixture for inhibiting reinforcing steel corrosion in steel-reinforced concrete designed for the microbial/industrial serviceenvironment.…”
Section: Inhibition Efficiency and Adsorption Isotherm Modelsmentioning
confidence: 99%
“…The surface coverage, Equation (6), applied to the experimental and predicted models were subjected to different adsorption isotherms such as the Langmuir, Flory-Huggins, Frumkin and Freundlich isotherms. Among these, the experimental and predicted models followed the Flory-Huggins [44][45] and the Frumkin [17,40] isotherms given respectively as:…”
Section: Inhibition Efficiency and Adsorption Isotherm Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference of synergistic effect was attributed to the film properties and polar effect 24) ; TEA addition couldn't form the film showing high film resistance and semiconductive properties, but DEA or MEA could build the film having relatively high film resistance and n-type semiconductive properties. Moreover, it can be explained that this behaviour was closely related to electron attractive group within the ethanolamines 25,26) . Electron attractive group is the functional group showing negative inductive effect.…”
Section: Resultsmentioning
confidence: 99%